Answer:
Step-by-step explanation:
y = -2x + 8
y = x - 1
solve by substitution
so y = -2x + 8......so sub -2x + 8 in for y back in the OTHER equation
-2x + 8 = x - 1 ........add 2x to both sides
-2x + 2x + 8 = x + 2x - 1.....combine like terms
8 = 3x - 1......add 1 to both sides
8 + 1 = 3x- 1 + 1....combine like terms
9 = 3x .....now divide both sides by 3
9/3 = (3/3)x.....simplify
3 = 1x....which is the same as 3 = x
so now that we know x is 3, sub that back into either of ur original equations to find y
y = x - 1
y = 3 - 1
y = 2
lets check it.....(3,2)
y = -2x + 8 y = x - 1
2 = -2(3) + 8 2 = 3 - 1
2 = -6 + 8 2 = 2 (correct)
2 = 2 (correct)
so ur solution is (3,2) <=====